The tectonic regime along the Andes: Present-day and Mesozoic regimes - Ramos, V.A. (2010)
The analyses of the main parameters controlling the present Chile-type and Marianas-type tectonic settings developed along the eastern Pacific region show four different tectonic regimes: (1) a nearly neutral regime in the Oregon subduction zone; (2) major extensional regimes as the Nicaragua subduction zone developed in continental crust; (3) a Marianas setting in the Sandwich subduction zone with ocean floored back-arc basin with a unique west-dipping subduction zone and (4) the classic and dominant Chile-type under compression. The magmatic, structural and sedimentary behaviours of these four settings are discussed to understand the past tectonic regimes in the Mesozoic Andes based on their present geological and tectonic characteristics. The evaluation of the different parameters that governed the past and present tectonic regimes indicates that absolute motion of the upper plate relative to the hotspot frame and the consequent trench roll-back velocity are the first order parameters that control the deformation. Locally, the influences of the trench fill, linked to the dominant climate in the forearc, and the age of the subducted oceanic crust, have secondary roles. Ridge collisions of seismic and seismic oceanic ridges as well as fracture zone collisions have also a local outcome, and may produce an increase in coupling that reinforces compressional deformation. Local strain variations in the past and present Andes are not related with changes in the relative convergence rate, which is less important than the absolute motion relative to the Pacific hotspot frame, or changes in the thermal state of the upper plate. Changes in the slab dip, mainly those linked to steepening subduction zones, produce significant variations in the thermal state, that are important to generate extreme deformation in the foreland. © 2009 John Wiley & Sons, Ltd.